Erector spinae plane block reduces postoperative nausea and vomiting: a systematic review and meta-analysis of 44 randomized trials - Zhao, Chong; Zhu, Minmin; Jian, Jinjin; Zeng, Jinfang (Frontiers in Medicine, 2026)
BackgroundPostoperative nausea and vomiting (PONV) is a prevalent complication and remains a significant clinical challenge. The erector spinae plane (ESPB) block has been shown to offer significant pain relief during and after surgical procedures, positioning it as a potentially beneficial anesthetic technique. However, limited evidence currently supports its effectiveness in reducing nausea and vomiting specifically. This meta-analysis aims to examine the impact of ESPB on PONV rates, assessing whether the block offers measurable benefits for this common postoperative issue, in addition to its recognized analgesic effects.MethodsTwo researchers conducted a comprehensive search across three databases—PubMed, Embase, and the Cochrane Central Register of Controlled Trials—using keywords such as “erector spinae plane block, meta-analysis, nausea, and vomiting” to identify all relevant literature. The data obtained from these studies were then analyzed through meta-analysis, utilizing Review Manager software to synthesize findings and assess overall outcomes.ResultsIn this meta-analysis, 44 trials involving 2,830 patients were analyzed. The ESPB was found to significantly decrease the incidence of nausea (risk difference (RD) = -0.16, 95% confidence interval (CI): -0.21—0.12) and vomiting (RD = -0.12, 95% CI: -0.17—0.07) compared to no ESPB. Additionally, ESPB decreased the dosage of morphine [standardized mean difference (SMD) = -0.86, 95% CI: -1.54 to -0.18], fentanyl (SMD = -2.96, 95% CI: -5.13 to -0.79), and tramadol (SMD = -1.43, 95% CI: -2.32 to -0.55) when compared to no ESPB. It also reduced VAS movement at 24 h (SMD = -1.58, 95% CI: -3.04 to -0.13) and lowered the occurrence of dizziness (RR = 0.43, 95% CI: 0.18–1.02), while prolonging the likelihood of itching (RR = 0.39, 95% CI: 0.25–0.61). We assessed the outcomes of nausea and vomiting with GRADE, and they were high to moderately certain, respectively. In addition, our analysis of trial sequences found adequate sample sizes for reductions in the incidence of nausea and vomiting.ConclusionOur meta-analysis found that ESPB may be able to reduce the incidence of nausea and vomiting and improve the quality of patients’ postoperative recovery and trial sequential analysis confirmed an adequate sample size for this conclusion.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024604805.